Using digital image processing and Unmanned Aerial Vehicle (UAV) for identifying ceramic cladding detachment in building facades - Sousa, Alcineide Dutra Pessoa de; Sousa, Gean Carlos Lopes de; Maués, Luiz Maurício Furtado (Ambiente Construído, 2022)
Facade maintenance actions are driven by results obtained in the inspection phase. Some methodological proposals aimed at optimizing the inspection process have been discussed, notably digital image processing (DIP) techniques associated with unmanned aerial vehicle (UAV) imagery. Using UAV speeds up the access to the inspected area, and DIP techniques help to automate the identification of pathological manifestations. This article aims to apply DIP techniques to detect areas where the ceramic cladding on building facades is detaching. The methodology referred to herein starts with the creation of a database (images) captured by cell phone and UAV. The object detection algorithm YOLO (You Only Look Once) was applied to the database images. The results indicated these techniques are very promising, with a 94% precision level in the tests performed. The precision index obtained indicates that the model is applicable in practice and discussions about its limitations help improve the proposed methodology.